THE IMPORTANCE OF THE MORPHOMETRIC RESEARCH OF BILE IN EARLY DIAGNOSTICS OF BILIOUS STONE FORMATION - Ya. M. Vakhrushev; N. A. Khokhlacheva; M. V. Moseeva; N. N. Glazyrina; A. V. Bystrova (SINAPS LLC, 2018)
The aim. To study the changes in the morphological picture of bile depending on the age of the patients and the possibility of using the information obtained in this way in the early diagnosis of gall stone formation.Material and methods. The study included 396 patients with stage I cholelithiasis, group 1 consisted of 125 patients of mature age (30-44 years), group 2 - 164 patients of middle age (45-59 years), group 3 - 107 elderly patients (60-74 years). The examined groups of patients were balanced by sex. In the verification of the diagnosis, in addition to general clinical data, results of echographic examination of the gallbladder were used. Multifractional duodenal sounding with the subsequent macroscopic, microscopic, morphometric, biochemical and physical investigation of bile is carried out. To study the morphological picture, features of the microstructure of gallbladder bile, the assessment of crystallograms was carried out.Results. When echographic examination of the gallbladder in all patients was determined signs of biliary sludge. The destabilization of bile is evidenced by an increase in cholesterol, a decrease in bile acids, a cholesterol ratio, an increase in its viscosity and surface tension. A morphometric study of the cystic bile of patients with early gallstone disease showed a decrease in the angle of inclination of liquid crystal lines, as well as the appearance of optically active inclusions, such as branched dendrites with lamellar branches, entangled fiber aggregates, shield-like aggregates and short branched dendrites. With an increase in the tendency of bile to stone formation, the optical activity of microcrystals increases, lamellar druses and branched plateau-like aggregates are determined.Conclusion The crystal-optic method of studying bile is highly sensitive, but at the same time simple in its execution and can be widely used in the early diagnosis of cholelithiasis. The degree of violation of the microstructure of bile increases with increasing age of patients.